The Hatfield Lunar Atlas Digitally Re-Mastered Edition - Cook, Anthony; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
The Hatfield Lunar Atlas has become an amateur lunar observer's bible since it was first published in 1968. A major update of the atlas was made in 1998, using the same wonderful photographs that Commander Henry Hatfield made with his purpose-built 12-inch (300 mm) telescope, but bringing the lunar nomenclature up to date and changing the units from Imperial to S.I. metric. However, with modern telescope optics, digital imaging equipment and computer enhancement new pictures can easily surpass what was achieved with Henry Hatfield's 12-inch telescope and a film camera. This limits the usefulness of the original atlas to visual observing or imaging with rather small amateur telescopes. The new, digitally re-mastered edition vastly improves the clarity and definition of the original photographs - significantly beyond the resolution limits of the photographic grains present in earlier atlas versions - while preserving the layout and style of the original publications. This has been achieved by merging computer-visualized Earth-based views of the lunar surface, derived from NASA's Lunar Reconnaissance Orbiter data, with scanned copies of Commander Hatfield's photographic plates, using the author's own software. The result is a The Hatfield Lunar Atlas for twenty-first century amateur telescopes.
Chapter 1: Introduction -- The Maps: Overlaps, Scales, Grids -- Nomenclature -- The Librartion Keys -- The Moon's Age and the Sun's Selenographic Colongitude -- The Digital Image Augmentation Process -- For Further Information -- Chapter 2: Lunar Observing Techniques -- Projects for Beginners -- Advanced Techniques -- References -- Chapter 3: Maps and Plates -- Chapter 4: Simulations of Sunrise and Sunset over Selected Features -- Appendices -- Appendix A: Details of Commander Hatfields's Photographic Plates -- Appendix B: TLP Identification Flow Charts -- Appendix C: Index of Named Formations.
Keywords: Physics; Planetology; Astronomy; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy; Planetology